2013
DOI: 10.1038/bjc.2013.192
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as potential new biomarkers for prostate cancer

Abstract: Since they were first described in the 1990s, circulating microRNAs (miRNAs) have provided an active and rapidly evolving area of current research that has the potential to transform cancer diagnostics and therapeutics. In particular, miRNAs could provide potential new biomarkers for prostate cancer, the most common cause of cancer in UK men. Current diagnostic tests for prostate cancer have low specificity and poor sensitivity. Further, although many prostate cancers are so slow growing as not to pose a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
137
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 32 publications
2
137
0
1
Order By: Relevance
“…Following the initial demonstration that elevated serum levels of miRNA-21 were associated with relapse-free survival of diffuse large B-cell lymphoma patients (13), several circulating miRNAs were identified as potential diagnostic and prognostic biomarkers for various types of cancer, including nasopharyngeal carcinoma (14) and glioma (15), as well as breast (6,16,17), gastric (18,19), prostate (20,21), pancreatic (22) and colorectal cancer (23). As a tumor screening marker, circulating miRNAs have several advantages, including the availability of serum samples and their stability during storage relative to that of tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial demonstration that elevated serum levels of miRNA-21 were associated with relapse-free survival of diffuse large B-cell lymphoma patients (13), several circulating miRNAs were identified as potential diagnostic and prognostic biomarkers for various types of cancer, including nasopharyngeal carcinoma (14) and glioma (15), as well as breast (6,16,17), gastric (18,19), prostate (20,21), pancreatic (22) and colorectal cancer (23). As a tumor screening marker, circulating miRNAs have several advantages, including the availability of serum samples and their stability during storage relative to that of tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43] miRNAs hold considerable promise to be exploited as highly accurate and functional prognostic serum markers of CaP stages and drug responses. 27,[44][45][46][47][48][49][50][51][52][53][54] They can encapsulate events within the tumor microenvironment, thereby overcoming the limitations of sampling error at biopsy. In parallel, it has become apparent that changes in miRNA regulation in tumors is translated to altered serum expression patterns and, therefore, offers an important diagnostic and prognostic therapeutic window.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have shown that miRNAs play a vital role in various biological processes which are essential for human life, including cell proliferation, differentiation, ageing and apoptosis 2, 3, 4, 5. In the meanwhile, evidence have demonstrated that miRNAs are related with a number of common neoplasms, such as breast neoplasms,6 lung neoplasms7 and prostate neoplasms 8. Therefore, the research on prediction of potential associations between miRNAs and diseases provides new opportunities to study the molecular mechanisms of diseases.…”
Section: Introductionmentioning
confidence: 99%